Water Content of Stingless Bee Honey Varies by Season - Andi Gita Maulidyah Indraswari Suhri; Irnayanti Bahar (Jurnal Biologi Tropis, 2023)
The relative humidity of the air in the region where honey is produced has a significant influence on the moisture content of the honey. The production season, feed source, nectar type and concentration, colony strength, and physical environmental conditions are all factors that influence honey's moisture content. The goal of this study was to determine the moisture content of honey collected over the course of a year to learn more about the quality and safety of honey. One hundred fifty samples of honey gathered from Bone, Indonesia, during both the wet and dry seasons were analyzed to assess the percentage of moisture present in the honey. Honey's physical properties, microbiological value, sensory qualities, and economic worth are all affected by its moisture content. At a temperature of 25 degrees Celsius, an Abbetype standard model refractometer was used to measure the refractive index (RI) in accordance with the method recommended by the International Honey Commission. Comparing honeys produced during the wet season with those produced during the dry season revealed that there is a statistically significant variation in the quantity of moisture that is present (p = 0.0029). This demonstrated that the moisture content of honey during the dry season had a substantially different value compared to the wet season at the 0.01 level (p = 0.00024). Using the F test, it was determined that there was not a significant difference in the amount of moisture contained in specific varieties of honey that were produced during the wet seasons and those that were produced during the dry seasons.